Awareness and Perception of the Artificial Intelligence in the Management of University Libraries in Nigeria. Issue 1 (20th April 2021) - Abayomi, Owolabi Kehinde; Adenekan, Fauziyah Nihinlolawa; Abayomi, Adeleke, Olateju; Ajayi, Taiwo Abosede; Aderonke, Adesina Olaitan
Abstract: Due to the growing presence of artificial intelligence (AI) in developed countries, this study investigates the awareness and perception about artificial intelligence in the management of university libraries in Nigeria. The study is a survey design that is based on both qualitative and quantitative approaches. The population of the study comprised eighty academic librarians from eight purposively selected university libraries in the country. The finding of the study revealed that academic librarians are aware of the existence of AI usage in the university libraries and that the fear of job loss is the major constraint they face in the adoption of the technologies; even though they are aware that the innovative technologies will enable efficient user satisfaction. The study recommends the need for academic librarians to make themselves relevant in this era of the fourth industrial revolution, by acquiring necessary skills that are in line with the technologies. It is also critical that library management educate academic librarians to understand that the adoption of AI in the library does not translate to the loss of jobs.